Efficiency-Morality Trade-Offs in Repugnant Transactions: A Choice Experiment - Julio Elias; Nicola Lacetera; Mario Macis (Institute for the Study of Labor (IZA), 2016)
Societies prohibit many transactions considered morally repugnant, although potentially efficiency-enhancing. We conducted an online choice experiment to characterize preferences for the morality and efficiency of payments to kidney donors. Preferences were heterogeneous, ranging from deontological to strongly consequentialist; the median respondent would support payments by a public agency if they increased the annual kidney supply by six percentage points, and private transactions for a thirty percentage-point increase. Fairness concerns drive this difference. Our findings suggest that cost-benefit considerations affect the acceptance of morally controversial transactions, and imply that trial studies of the effects of payments would inform the public debate.
Keywords: C91; D01; D63; D64; I11; 330; repugnant transactions; efficiency; morality; markets; preferences